Assessment of IT Governance Capability Level Using the COBIT 2019 Framework: A Case Study of XYZ Institution - Amry, Anshari; Wirani, Yekti; Sucahyo, Yudho Giri (Program Studi Informatika, 2025)
XYZ Institution recognizes Information Technology (IT) as a strategic enabler essential for achieving organizational objectives and advancing its digital transformation objectives. IT governance plays a critical role in ensuring alignment between the utilization of IT and the achievement of strategic objectives. In today